2024
DOI: 10.1002/ctm2.1599
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neutrophils: Mechanism and advances in cancer therapy

Shuaixi Yang,
Jiachi Jia,
Fuqi Wang
et al.

Abstract: BackgroundCancer is a thorny problem which cannot be conquered by mankind at present and recent researchers have put their focus on tumor microenviroment. Neutrophils, the prominent leukocytes in peripheral blood that accumulate in tumours, serves as frontline cells in response to tumour progression owing to the rapid development of micro biotechnology. Hence, targeted therapy with these neutrophils has made targeting treatment a promising field in cancer therapy.Main bodyWe broadly summarise some studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 121 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…According to their surface marker molecules, some promote tumor growth, while others inhibit tumor progression. Therefore, for different neutrophil phenotypes, some studies targeting neutrophils have become the focus of research (44). Wang et al (45) found that CD300ld expressed on neutrophils is a key immunosuppressive factor in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…According to their surface marker molecules, some promote tumor growth, while others inhibit tumor progression. Therefore, for different neutrophil phenotypes, some studies targeting neutrophils have become the focus of research (44). Wang et al (45) found that CD300ld expressed on neutrophils is a key immunosuppressive factor in the TME.…”
Section: Discussionmentioning
confidence: 99%
“… 93 In accordance with cytokine production patterns and effector functions, TANs are able to polarize into two populations: the antitumorigenic “N1” phenotype or the protumorigenic “N2” phenotype. 94 , 95 In case of sterile inflammation, N1 neutrophils predominate during an acute phase and provoke an exaggerated inflammatory reaction through the secretion of NETs. However, as later phases, there is a progressive increase in the proportion of N2 neutrophils, which exerts a beneficial influence by means of the secretion of anti‐inflammatory factors.…”
Section: Molecular Mechanisms Of Nets Formationmentioning
confidence: 99%